Complex probiotics can reduce diarrhea by boosting immunity and balancing gut microbiota in weaned piglets - Wang, Mingyu; Zhou, Xian; Hübertz Birch Hansen, Lea; Sheng, Yongshuai; Yu, Bing; He, Jun; Yu, Jie; Zheng, Ping (Frontiers in Immunology, 2025)
PurposeSOLVENS (SLV) is a zootechnical feed additive based on viable spores of Bacillus licheniformis and Bacillus subtilis. This study aimed to evaluate the effects of SLV on the intestinal health of weaned piglets.MethodsA total of 360 healthy 24-day-old weaned Duroc × Landrace × Yorkshire piglets were allocated to three treatment groups based on body weight and sex: T1 (Control, CON), T2 (SLV 200, 6.5×108 CFU per kg feed), and T3 (SLV 400, 1.3×109 CFU per kg feed). Each treatment consisted of 30 replicates with four pigs per replicate, and the experiment lasted 42 days. Piglets were fed mash pre-starter feed (days 1–14) and mash starter feed (days 15–42). Growth performance, fecal microorganisms, serum immunity, and intestinal barrier function were assessed. Experimental data were analyzed using SPSS 27.0 for one-way ANOVA, and multiple comparisons were made using the DUNCAN method.ResultsCompared with the control, SLV 200 and SLV 400 significantly reduced diarrhea rate (P < 0.05). SLV 200 increased fecal Lactobacilli and decreased Escherichia coli on day 14 (P < 0.05), while SLV 400 elevated Lactobacilli on days 14 and 42 and reduced E. coli on day 14 (P < 0.05). SLV 200 increased fecal sIgA and serum IgG on day 42 (P < 0.05), whereas SLV 400 elevated serum IgG and IgM on day 14 (P < 0.05) and serum IgA on day 42 (P < 0.05). Additionally, SLV 200 downregulated ileal interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) gene expression (P < 0.05), and SLV 400 reduced TNF-α expression (P < 0.05).ConclusionDietary supplementation with SLV improved intestinal health by modulating gut microbiota and enhancing immunity in weaned piglets.